2000
DOI: 10.1111/j.1553-2712.2000.tb00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Complications of a Retrograde Intubation in a Trauma Patient

Abstract: Abstract. The authors report the case of an elder woman involved in a motor vehicle collision (MVC) requiring emergent intubation using the technique of retrograde intubation (RI). Since RI is a blind technique, potential complications arising from its use are numerous and may result in increased morbidity and mortality. Such was the case of this RI that involved incorrect placement of the endotracheal tube (ETT), resulting in suboptimal ventilation and increased morbidity. Additionally, this case illustrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
0
15
0
2
Order By: Relevance
“…While some authors recommend a greater degree of tension be held on the retrograde wire to increase the odds of ETT passage [8], this tension may result in bleeding, edema, and trauma to the local tissues. Others recommend rotating the tube as it approaches the cords [43], but this evidence is anecdotal at best. A puncture site caudal to the cricothyroid membrane would seem to offer the advantage of a greater distance between the retrograde wire and the impinging structures, as well as a reduction in the acuity of the angle the ETT must negotiate into the trachea.…”
Section: Discussionmentioning
confidence: 99%
“…While some authors recommend a greater degree of tension be held on the retrograde wire to increase the odds of ETT passage [8], this tension may result in bleeding, edema, and trauma to the local tissues. Others recommend rotating the tube as it approaches the cords [43], but this evidence is anecdotal at best. A puncture site caudal to the cricothyroid membrane would seem to offer the advantage of a greater distance between the retrograde wire and the impinging structures, as well as a reduction in the acuity of the angle the ETT must negotiate into the trachea.…”
Section: Discussionmentioning
confidence: 99%
“…Tracheal tubes made of polyvinyl chloride when compared with armoured and silicon tubes have been shown to exert considerably higher pressure on the point of contact [66]. Application of overzealous pressure has resulted in folding of the tube inside the airway [67].…”
Section: Depth Of Insertionmentioning
confidence: 99%
“…The tip of the tube is harnessed either by retrograde guide stitched to it (4) or by a loop of retrograde guide tightened around it (5) and is then pulled down from the pharynx into the larynx. Suction catheters (cooled for added firmness) [66,67] Eschmann TM guide modified by severing the end [72] Guide wire sheath [3] Multi-lumen catheter [14] Airway exchange catheter [73] Custom made guide made by Cook (Cook Critical care, Bloomington, IN, USA) Flexible fibreoptic endoscope [13,25,[79][80][81] Anchor AG + RG Figure 4 In addition to an anterograde guide (AG) over retrograde guide (RG) an anchoring introducer is passed through the tracheal tube into the trachea. retrograde guide is released.…”
Section: Prevention Of Dislodgement Of the Tracheal Tubementioning
confidence: 99%
“…1 In an emergency department review of 1368 charts, Gill et al 2 found that retrograde tracheal intubation was attempted in 8 patients and was successful in only 4. The usual technique for retrograde intubation is to pass a long guidewire through the cricothyroid membrane and angle it cranially for it to pass through the vocal cords and appear in the oropharynx, after which an endotracheal tube and/or fiberoptic scope is railroaded over the wire.…”
Section: Commentmentioning
confidence: 99%